Prospects of development of the Russian innovative system through the prism of qualitative methods - V. V. Volchik; E. V. Fursa; A. I. Maskaev (Russian Journal of Economics and Law, 2021)
Objective: to examine the influence of positive and critical narratives in the media, illustrating the problems and strengths of the Russian innovation system development, on the formation of public opinion.Methods: the methodology of narrative analysis of economics and original institutionalism is used in relation to the national innovation system.Results: with the help of narrative analysis, we analyzed 43 media outlets from Internet sources selected in accordance with the Medialogiya rating “Federal Mass Media: 2020” for the period from 01.01.2010 to 01.07.2021. A range of significant issues is highlighted which affect the innovative development, mentioned by media addressees and the Russian innovation system actors (policymakers, business, academic circles). Four types of positive narratives about the Russian innovation system are identified: 1) narratives about significant technological achievements; 2) narratives about the development of innovative infrastructure; 3) narratives that tell about the public recognition of the success of the Russian innovation system actors at professional conferences or by the state; 4) futurological narratives about prospects in the medium or long term.Scientific novelty: consists in the development of the narrative economics approach and the concept of public arenas for the analysis of the Russian innovation system with the help of mass media.Practical significance: the identified positive narratives allow studying the best practices and rules that contribute to the integration of science, government and business into a single innovation system in order to further upscale the positive experience to the entire economy. Positive narratives also contribute to the formation of a favorable innovation space and public opinion in Russia.